Extramammary Paget’s Disease in the Genital Area of a Male: A Case Report and Review of the Literature - Zhao, Dan; Wen, Bo-ping; Xu, Sen-yin (Frontiers in Oncology, 2021)
Extramammary Paget's disease (EMPD) is an uncommon intraepithelial malignancy that is rarely found in the male. Currently there is very little knowledge pertaining to EMPD imaging, particularly in cases that involve the scrotum. Here, a 67-year-old man with lichenification on his left scrotum confirmed to be EMPD was reviewed. Bloodwork did not return a positive result, but syphilis-specific antibodies were found. Conventional high-frequency ultrasound (US) and contrast-enhanced ultrasound (CEUS) imaging were utilized to determine the lesion size and blood perfusion. In the present case, the lesion’s size and involvement was vividly depicted by CEUS, while results obtained by conventional US were grossly underestimated. Consequently, multimodal imaging assessment is likely to provide more accurate diagnoses for uncommon diseases, such as EMPD, and to aid in clinical decision-making.